Determinants of local government debt in the Federation of Bosnia and Herzegovina - Moćević Amina; Lazović-Pita Lejla (Financial Internet Quarterly, 2024)
The theory of fiscal federalism suggests that debt of subcentral levels of government is closely related to the internal organization of the country, defined through intergovernmental fiscal relations. Due to a great importance of subcentral levels of government in the theory and practice of fiscal federalism, the aim of the research is to empirically investigate the determinants of local government units’ (LGUs) debt in the Federation of Bosnia and Herzegovina (FBiH). Based on panel data from 2011 to 2019 and by using a generalized method of moments (GMM), we estimate the model using sets of fiscal, institutional, economic, and demographic variables. The results indicate that the debt of LGUs in FBiH is significantly determined by intergovernmental fiscal relations defined through a group of fiscal and institutional variables and demographic factors. Significant determinants of LGU’s debt in FBiH in the both short and a long term include financing of special expenditure needs of some LGUs together with LGUs within a canton with special expenditure needs. Furthermore, transfers from other government levels are also significant in the short and a long term. Based upon our results, we conclude with several policy implications important for the upcoming intergovernmental decision-making processes in FBiH.